METODE TAKHRIJ HADIS PADA ILMU HADIS: MELACAK KUALITAS HADIS KEUTAMAAN MENIKAH - Arif Sugitanata; Marhumah (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Takhrij al-Hadis is a search or search for traditions from various original sources by presenting the complete matan and sanad and then examining the quality of the hadith. In this study, researchers explore the quality of the Hadith on the virtues of marriage. The research uses a literature study as a study knife whose primary data is processed qualitatively with a descriptive-analytical method where it is sourced from books and journals related to takhrij hadith on the Hadith on the virtues of marriage and the Hadith on marriage guardians. This study found that the Hadith about the virtue of marriage has the status of Shohih and. This is because there are no defects in the narrators who are on average tsiqqoh narrators. This Hadith can be used as an argument and legal basis for Muslims.